2010
DOI: 10.1111/j.1728-4465.2010.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Equity Analysis: Identifying Who Benefits from Family Planning Programs

Abstract: This study examines current disparities in access to family planning services in developing countries with data drawn from 64 Demographic and Health Surveys conducted between 1994 and 2008. The percent of demand satisfied is used as a proxy measure for access to family planning. In all regions, married women aged 15-19 have greater difficulty than older women in meeting their need for contraceptive services. Inequities in the percent of demand satisfied among individuals of varying economic status, area of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
(5 reference statements)
4
26
0
2
Order By: Relevance
“…Gabrysch and Campbell noted that these barriers frequently interact and further identified that groups in remote areas often face worse health infrastructure and transport, limited access to information, poverty and strong traditional systems [8]. Likewise, these factors influence the utilisation of antenatal care, family planning, and care for common childhood illnesses with greater impact on remote families [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Gabrysch and Campbell noted that these barriers frequently interact and further identified that groups in remote areas often face worse health infrastructure and transport, limited access to information, poverty and strong traditional systems [8]. Likewise, these factors influence the utilisation of antenatal care, family planning, and care for common childhood illnesses with greater impact on remote families [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the access as a barrier, quality service is critical for effective and sustained use [7]. Inequity in those unserved is marked [8-10] in both utilisation of and ability to demand family planning [10,11]. In a sample of 41 developing countries the poorest wealth quintile was found to have twice the number of unwanted births than the richest (1.1 vs. 0.5) and endure less access to information and health workers [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 41 developing countries the poorest wealth quintile was found to have twice the number of unwanted births than the richest (1.1 vs. 0.5) and endure less access to information and health workers [10]. In another analysis of 64 developing countries, inequitable unmet need for family planning was associated with area of residence, age and woman’s education, in addition to wealth [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Gaps in attaining universal access to reproductive health and FP are most apparent among the least educated and poorest segments of the population [25]. Across multiple countries and in both urban and rural settings, young, poorer, and uneducated women are less likely to use modern FP and to have an institutional delivery [35].…”
Section: Introductionmentioning
confidence: 99%
“…Gaps in attaining universal access to reproductive health and FP are most apparent among the least educated and poorest segments of the population [25]. Across multiple countries and in both urban and rural settings, young, poorer, and uneducated women are less likely to use modern FP and to have an institutional delivery [35]. These gaps in FP use and institutional delivery may be related to social barriers in contexts where mothers-in-law play an important role in household decision-making [68].…”
Section: Introductionmentioning
confidence: 99%